Kajian Karakteristik dan Energi pada Pirolisis Limbah Plastik Low Density Polyethylene (LDPE) - Novarini; Sigit Kurniawan; Rusdianasari; Yohandri Bow (Jurnal Teknik Kimia dan Lingkungan, 2021)
Low-Density Poly Ethylene (LDPE), plastic waste cannot be broken down by microorganisms in the soil, has no sale value, so it is buried in the final waste disposal site. One of the plastic waste treatment methods is the pyrolysis process. The purpose of this study was to determine the type of fuel oil from pyrolysis products and to determine the energy efficiency produced against the highest fuel use. The pyrolysis equipment used is 1 reactor unit and 1 condenser unit. The characteristics of the fuel oil product analyzed are the cetane index, density, sulfur content, kinematic viscosity, flash point, and caloric value of the pyrolysis process which varies the combustion temperature in the reactor by 200°C, 250°C, 300°C and the process in the reactor, with and without the use of natural zeolite catalysts 1% against 2.5 kg of LDPE plastic waste for 6 hours. After the type of fuel produced is identified, an energy efficiency assessment of the fuel product is carried out on the use of fuel in the pyrolysis process. The results analysis show that the all product of fuel oil is a kerosene-type of fuel. The highest efficiency of 72.51% is the kerosene produced in pyrolysis using a catalyst at a temperature of 250°C with an energy value ratio of 20,402 kcal for kerosene from pyrolysis of LDPE plastic waste and 28,137 kcal for the use of Liquefied Petroleum Gas (LPG) fuel in the pyrolysis process. Pyrolysis using a 1% zeolite catalyst at 250°C has proven to be an efficient and sustainable way to treat LDPE waste into kerosene fuel.